2017
DOI: 10.1186/s12883-017-0836-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the capsaicin 8% patch in the management of peripheral neuropathic pain in European clinical practice: the ASCEND study

Abstract: BackgroundIn randomised studies, the capsaicin 8% patch has demonstrated effective pain relief in patients with peripheral neuropathic pain (PNP) arising from different aetiologies.MethodsASCEND was an open-label, non-interventional study of patients with non-diabetes-related PNP who received capsaicin 8% patch treatment, according to usual clinical practice, and were followed for ≤52 weeks. Co-primary endpoints were percentage change in the mean numeric pain rating scale (NPRS) ‘average daily pain’ score from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 28 publications
2
49
0
6
Order By: Relevance
“…We chose to perform this analysis in patients treated with capsaicin 8% cutaneous patch because the application is performed in specialized facilities by trained health professionals, which guaranteed that all patients would correctly receive the correct dose of the product. In addition, the effectiveness of the patch has been proven in several randomized clinical trials and non‐interventional studies (Backonja et al, ; Clifford et al, ; Hansson, Jensen, Kvarstein, & Strömberg, ; Irving et al, ; Maihofner & Heskamp, ; Mankowski et al, ; Simpson et al, ). Finally, thanks to its low systemic exposure and rapid elimination following application (Pickering, Martin, Tiberghien, Delorme, & Mick, ), few side effects, and in particular cognitive side effects that could interfere with mood or quality of life or lead to premature treatment discontinuation, were expected.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to perform this analysis in patients treated with capsaicin 8% cutaneous patch because the application is performed in specialized facilities by trained health professionals, which guaranteed that all patients would correctly receive the correct dose of the product. In addition, the effectiveness of the patch has been proven in several randomized clinical trials and non‐interventional studies (Backonja et al, ; Clifford et al, ; Hansson, Jensen, Kvarstein, & Strömberg, ; Irving et al, ; Maihofner & Heskamp, ; Mankowski et al, ; Simpson et al, ). Finally, thanks to its low systemic exposure and rapid elimination following application (Pickering, Martin, Tiberghien, Delorme, & Mick, ), few side effects, and in particular cognitive side effects that could interfere with mood or quality of life or lead to premature treatment discontinuation, were expected.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the heterogeneous patient population from a diagnostic perspective may have included subgroups of patients less susceptible to respond to this type of treatment. For example, in another real‐world study of the capsaicin 8% patch that included seven European countries, patients with post‐operative and post‐traumatic neuropathic pain had less improvement in pain over 8 weeks compared with patients with other aetiologies including postherpetic neuralgia and neuropathic back pain (Mankowski et al., ). Direct comparisons to other studies are not possible due to differences in trial design (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the number needed to treat to achieve a 50% reduction in pain was 10.6 (Finnerup et al., ). The outcomes of single applications of the capsaicin 8% patch for the treatment of PNP have been documented in clinical practice (Maihofner and Heskamp, , ; Haanpaa et al., ), and recently, repeat applications were found to be effective and well tolerated in a 52‐week real‐world European study (Mankowski et al., ).…”
Section: Introductionmentioning
confidence: 98%
“…This desensitization allows the use of capsaicin as an analgesic [19]. Long term treatment have been studied along several prospective cohort studies [20][21][22] CP8% treatment have been studied up to 52 weeks of follow-up, with repeated patch application. In these studies no sensory changes in the skin was found after repeated treatment.…”
Section: Introductionmentioning
confidence: 99%